1946
DOI: 10.6028/jres.037.002
|View full text |Cite
|
Sign up to set email alerts
|

A study of the damaging effect of fatigue stressing on SAE X4130 steel

Abstract: The damaging effect of fatigue stressing above the endurance limit was investigated with notched specimens of SAE X4130 steel. The damage was measured by the decrease in endurance at another stress. A deflection method for detecting the formation of a fatigue crack permitted the damage measurement to be limited chiefly to the pre crack stage. The results showed that the apparent rate of damage depends on the stress history. If the prestress is higher than the test stress, the damage occurs rapidly at first, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1949
1949
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Bennett [11] has shown that notches reduce the endurance limit of normalized X4130 steel approximately 20 p ercent and that fine cracks reduce the endurance limit by more than 50 p er cent. The presence of cracks in the chromium plated at 55° and 70° C might explain the r eduction in the endurance limits of steel specimens plated at these temperatures.…”
Section: Discussion Of Causes Of Effects Of Chromiummentioning
confidence: 99%
“…Bennett [11] has shown that notches reduce the endurance limit of normalized X4130 steel approximately 20 p ercent and that fine cracks reduce the endurance limit by more than 50 p er cent. The presence of cracks in the chromium plated at 55° and 70° C might explain the r eduction in the endurance limits of steel specimens plated at these temperatures.…”
Section: Discussion Of Causes Of Effects Of Chromiummentioning
confidence: 99%
“…In previous investigations at the Bureau small cracks have been detected by (1) measurement of the increased deflection under the test load [9], (2) observation of the specimen under stroboscopic ligh t [6], and (3) the use of fracture wires [10] .…”
Section: Materials and Test Methodsmentioning
confidence: 99%
“…The latter factor likely plays an important role in the appearance of the coaxing effect in ferritic steels. 10) Assuming that strain-age hardening is important, the coaxing effect must be a kinetic problem. More specifically, the coaxing effect is considered to depend on the aging time (not the number of cycles), the plastic strain at a crack tip, and the carbon concentration.…”
Section: Intrinsic Factors That Trigger the Coaxing Effect In Binary mentioning
confidence: 99%
“…Interestingly, a specimen fatigued at the fatigue limit does not show failure even after a slight increase in the stress amplitude. 9,10) This phenomenon is called the "coax-…”
Section: Introductionmentioning
confidence: 99%